The Effects of Self- Acupressure on Pain and Sleep Quality in Patients With Coronary Artery Disease: A Randomised Controlled Trial - Basak, Seda; Turan, Guelcan Bahcecioglu; Oezer, Zuelfuenaz (Elsevier Science Inc, 2025)
Purpose: The most important cause of death among cardiovascular diseases is coronary artery disease (CAD). Pain and insomnia symptoms are the most common symptoms in CAD patients. Acupressure is used in patients with CAD as one of the energy-based complementary and alternative methods. This study was conducted to investigate the effects of self-acupressure on pain and sleep quality in patients with coronary artery disease. Design: This is a randomised controlled trial. Methods: This study was conducted between June and August 2021 with a total of 80 participants, 40 in the intervention and 40 in the control group. The participants in the intervention group were asked to perform a total of 16 sessions for 4 weeks, 2 days a week in the morning and afternoon, for a total of 23 minutes, depending on the preparation and compression time to be performed on 5 points. The control group did not receive any intervention during the study. Data were collected by using Descriptive Information Form, Visual Analogue Scale (VAS) and Pittsburgh Sleep Quality Index (PSQI). Results: After self-acupressure, the VAS total score of the intervention group decreased significantly compared to the control group (t = -11.861; p < .05). After intervention PSQI total and subscale mean scores of the intervention group decreased significantly compared to the control group (t = -7.767; p < .05). It can be seen that self-acupressure application has a negative and significant effect on PSQI total mean scores and VAS total mean score of patients (p < .05). Conclusion: The results of this study showed that self-acupressure was effective in improving the pain and sleep quality of patients with coronary artery disease. Clinical Implications: Self-acupressure is an accessible and inexpensive method, it is recommended to be supported and maintained in the management of coronary artery disease in nursing practice. (c) 2024 American Society for Pain Management Nursing. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Nurse; Pain; Self-acupressure; Sleep quality